Linear transformation : examples and solutions - Shah, Nita H.; Chaudhari, Urmila B. (Boca Raton : CRC Press, 2021)
This book introduces linear transformation and its key results, which have applications in engineering, physics, and various branches of mathematics. Linear transformation is a difficult subject for students. This concise text provides an in-depth overview of linear trans-formation. It provides multiple-choice questions, covers enough examples for the reader to gain a clear understanding, and includes exact methods with specific shortcuts to reach solutions for particular problems. Research scholars and students working in the fields of engineering, physics, and different branches of mathematics need to learn the concepts of linear transformation to solve their problems. This book will serve their need instead of having to use the more complex texts that contain more concepts then needed. The chapters mainly discuss the definition of linear transformation, properties of linear transformation, linear operators, composition of two or more linear transformations, kernels and range of linear transformation, inverse transformation, one-to-one and onto transformation, isomorphism, matrix linear transformation, and similarity of two matrices.
Chapter 3 Inverse Linear Transformation -- 3.1 One-One Transformation -- 3.1.1 Some Important Results -- 3.2 Onto Transformation -- 3.3 Isomorphism -- 3.4 Inverse Linear Transformation -- Exercise Set 3 -- Answers to Exercise Set 3 -- Chapter 4 Matrices of General Linear Transformations -- 4.1 Matrix of General Transformations -- 4.2 Similarity -- 4.2.1 Effect of Changing Bases on Matrices of Linear Operators -- Exercise Set 4 -- Answers to Exercise Set 4 -- Multiple-Choice Questions on Linear Transformation -- Bibliography -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Algebras, Linear -- Problems, exercises, etc; Linear operators; MATHEMATICS / Applied; TECHNOLOGY / Operations Research; BUSINESS & ECONOMICS / Operations Research